2016
DOI: 10.1016/j.neulet.2016.02.033
|View full text |Cite
|
Sign up to set email alerts
|

A novel dual NO-donating oxime and c-Jun N-terminal kinase inhibitor protects against cerebral ischemia–reperfusion injury in mice

Abstract: The c-Jun N-terminal kinase (JNK) has been shown to be an important regulator of neuronal cell death. Previously, we synthesized the sodium salt of 11H-indeno[1,2-b]quinoxalin-11-one (IQ-1S) and demonstrated that it was a high-affinity inhibitor of the JNK family. In the present work, we found that IQ-1S could release nitric oxide (NO) during its enzymatic metabolism by liver microsomes. Moreover, serum nitrite/nitrate concentration in mice increased after intraperitoneal injection of IQ-1S. Because of these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 59 publications
5
45
0
3
Order By: Relevance
“…c-Jun N-terminal kinases (JNK) are important stress responsive kinases, and JNK signaling is the shared pathway linking microglia activation, neuroinflammation and cerebral ischemic injury [18, 19]. Previous studies demonstrated that JNK inhibition by specific inhibitor (e.g., IQ-1S and SP600125) contributes to reduce cerebral ischemia-reperfusion injury in mice [20, 21]. JNK-IN-8, an adenosine triphosphate-competitive irreversible pan-JNK inhibitor, exerts a protective role in inhibiting traumatic brain injury and cancer cell grow [22, 23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…c-Jun N-terminal kinases (JNK) are important stress responsive kinases, and JNK signaling is the shared pathway linking microglia activation, neuroinflammation and cerebral ischemic injury [18, 19]. Previous studies demonstrated that JNK inhibition by specific inhibitor (e.g., IQ-1S and SP600125) contributes to reduce cerebral ischemia-reperfusion injury in mice [20, 21]. JNK-IN-8, an adenosine triphosphate-competitive irreversible pan-JNK inhibitor, exerts a protective role in inhibiting traumatic brain injury and cancer cell grow [22, 23].…”
Section: Resultsmentioning
confidence: 99%
“…Another study demonstrated that SP600125 attenuated subarachnoid hemorrhage-cerebral vasospasm through a suppressed inflammatory response [33]. IQ-1S releases NO during its oxidoreductive bioconversion and improves stroke outcome in a mouse model of cerebral reperfusion [20]. Noteworthily, different JNK inhibitor exerts diverse physiological properties because of targeting different members of the JNK family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the reperfusion period, mice were examined for neurologic deficits using a 4‐point scale before being humanely killed. Neurologic outcomes were graded as: 0, normal; 1, forepaw monoparesis; 2, circling to right; 3, falling to right; and 4, no spontaneous walking and depressed consciousness (45). The brain was cut into 2 mm thick coronal blocks and stained in the dark with 2, 3, 5‐triphenyltetrazolium chloride for 1 h at 37°C, and the infarct volume was calculated (46).…”
Section: Methodsmentioning
confidence: 99%
“…Сегодня следует учитывать частое сочетание кардиальной патологии у пациентов с инсультом, поэтому оценка фармакологической модуляция JNK-активности является актуальной как для первичной, так и вторичной профилактики сердечнососудистых и цереброваскулярных заболеваний. Перспективность нейропротекторных и кардиопротекторных препаратов уже доказана, поскольку контроль JNK-активности происходит на уровне фосфорилирования и дефосфорилирования [6,7,8,11], а препараты, которые являются NO-донорским оксимом и ингибитором JNK, проявляют двойные эффекты, способствующие нейропротекции [11]. Точные молекулярные механизмы модуляции передачи сигналов JNK при ишемии или реперфузии остаются сегодня неясными для многих агентов, демонстрирующих нейропротекторный и кардиопротекторный эффект, что открывает путь для создания новых терапевтических подходов с безопасным профилем эффективности при одновременном сочетании острой и хронической патологии головного мозга и сердца [9,10,11].…”
Section: свиридова нкunclassified